CHARACTERISTICS OF WATER QUALITY AND GROWTH PERFORMANCE OF VANNAMEI SHRIMP (Litopenaeus vannamei) IN A HOUSEHOLD-SCALE BIOFLOC SYSTEM IN ALUE NAGA BANDA ACEH: KARAKTERISTIK KUALITAS AIR DAN PERFORMA PERTUMBUHAN UDANG VANAME (Litopenaeus vannamei) PADA SISTEM BIOFLOK SKALA RUMAH TANGGA DI ALUE NAGA BANDA ACEH - Nanda Fitriah; Humeira; Marysha Amelia; Rizka Maula (ROCE : Jurnal Pertanian Terapan, 2026)
This study aimed to analyze the water quality characteristics and growth performance of vannamei shrimp (Litopenaeus vannamei) cultured in a household-scale biofloc system in Alue Naga, Banda Aceh. Observations were conducted in two round ponds over an 80-day culture period, covering water quality parameters (temperature, pH, dissolved oxygen, salinity, transparency, and floc volume) and growth parameters (ABW, ADG, survival rate, and FCR). The results showed that all water quality parameters remained within the optimal range for vannamei shrimp culture, with mean temperatures of 27.25±0.91°C (Pond 1) and 27.83±0.69°C (Pond 2), pH of 7.35±0.15 and 7.34±0.13, and dissolved oxygen of 6.53±0.30 and 6.49±0.26 mg/L. Shrimp growth performance showed a consistent increase in ABW from 1.6 and 1.4 g to 12.3 and 11.7 g at DOC 80, with ADG ranging from 0.14–0.26 g/day and relatively efficient FCR values (0.95 and 1.02). However, the survival rate declined to 52% and 57%, lower than the ideal target of 80%. These findings indicate that the household-scale biofloc system maintained stable water quality and supported satisfactory shrimp growth, although the survival rate remains a limiting factor requiring further improvement.